The Model of Development of Professional and Spiritual Skills in Students on the Basis of the Work "Ma'orif" by Sayyid Burhoniddin Muhaqqiq Tirmizi (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This study was devoted to the development of professional and spiritual skills of students on the basis of the work "Ma'arif" by Sayyid Burhoniddin Muhaqqiq Tirmizi. The study developed a model for the formation of students' moral maturity, inner responsibility, self-awareness and social activity along with their professional competence by combining the mystical and educational heritage with modern pedagogical approaches. This model is based on person-centered, axiological, competent, and integrative approaches and includes target, meaningful, functional, and outcome components. The ideas of devotion, honesty, patience, humility, science and unity of action in the work "enlightenment" are justified as an important source of the development of spiritual qualities necessary in the professional activity of students. The results of the research are of practical value in the effective organization of the process of spiritual and ethical education in higher educational institutions, as well as the formation of students' professional responsibility and moral awareness.